Efficacy of phosphodiesterase type 5 inhibitors in univentricular congenital heart disease: the SV‐INHIBITION study design. (9th March 2020) - Amedro, Pascal; Gavotto, Arthur; Abassi, Hamouda; Picot, Marie‐Christine; Matecki, Stefan; Malekzadeh‐Milani, Sophie; Levy, Marilyne; Ladouceur, Magalie; Ovaert, Caroline; Aldebert, Philippe; Thambo, Jean‐Benoit; Fraisse, Alain; et al.
Abstract: Aims: In univentricular hearts, selective lung vasodilators such as phosphodiesterase type 5 (PDE5) inhibitors would decrease pulmonary resistance and improve exercise tolerance. However, the level of evidence for the use of PDE5 inhibitors in patients with a single ventricle (SV) remains limited. We present the SV‐INHIBITION study rationale, design, and methods. Methods and results: The SV‐INHIBITION trial is a nationwide multicentre, randomized, double blind, placebo‐controlled, Phase III study, aiming to evaluate the efficacy of sildenafil on the ventilatory efficiency during exercise, in teenagers and adult patients (>15 years old) with an SV. Patients with a mean pulmonary arterial pressure >15 mmHg and a trans‐pulmonary gradient >5 mmHg, measured by cardiac catheterization, will be eligible. The primary outcome is the variation of the VE/VCO2 slope, measured by a cardiopulmonary exercise test, between baseline and 6 months of treatment. A total of 50 patients are required to observe a decrease of 5 ± 5 points in the VE/VCO2 slope, with a power of 90% and an alpha risk of 5%. The secondary outcomes are clinical outcomes, oxygen saturation, 6 min walk test, SV function, NT‐proBNP, peak VO2, stroke volume, mean pulmonary arterial pressure, trans‐pulmonary gradient, SF36 quality of life score, safety, and acceptability. Conclusions: The SV‐INHIBITION study aims to answer the question whether PDE5 inhibitors should be prescribed in patients with an SV. This trial has been built focusing on the three levels of research defined by the World Health Organization: disability (exercise tolerance), deficit (SV function), and handicap (quality of life).